Evaluación de los parámetros de operación del alimentador primario Juan de Salinas Nro. 0213 perteneciente a la subestación San Cayetano de la EERSSA. - Pineda Cabrera, Ángel Luis (2014)
This project includes the evaluation of the operating parameters of the primary feeder Juan Salinas is to determine factors such as power factor fp, voltage drop ∆p, power loss ∆p, loss of energy ∆w and curves consumption, and also identifies possible nodes that present some problems with the distribution of electricity which generates losses for EERSSA. Technical information necessary for the development of this thesis project was compiled, likewise the EERSSA provided information about energy consumption in the primary feeder Juan de Salinas, with which it formed a database and using the respective analysis curve obtained high demand for the feeder. In this thesis as programs that facilitated its realization as ArcGIS, showing us the exact geographical location of each of the components of the distribution circuit, plus Study Program Distribution (EDIS) was used, the same as we facilitates the analysis of primary distribution circuits, where after entering the database was analyzed and simulated the behavior of the circuit.